Risk Factor Analysis of HIV/AIDS Incidence in General Hospital - Fera Novitry; Tiara Sari (LPPM STIKES Al-Ma'arif Baturaja, 2024)
The problem of HIV (Human Immunodeficiency Virus) and AIDS (Acquired Immune Deficiency Syndrome) is a health challenge almost all over the world. The impact is not only health but also in terms of economic, social, psychological, and will also affect reproductive health. Some of the causes of HIV/AIDS include occupation, knowledge, attitude, age, gender, education, household economic status, access to information media, communication with parents, and the presence of friends who behave at risk, sexual behaviour. This study used Cross Sectional research design. The population of this study were patients who visited the skin and genital disease poly room. The sample in this study amounted to 80 people. Sampling was done by non probability sampling with quota technique. Data collection tools using questionnaires and HIV / AIDS test results. Data analysis using Chi Square. Data were collected by structured interviews using questionnaires for specific questions supported by observation. Bivariate analysis using chi square. The results of the analysis showed that there was a relationship between sexual behaviour (ρ value 0.000), occupation (ρ value 0.000), knowledge (ρ value 0.000), family history (ρ value 0.034), marital status (ρ value 0.000) to the incidence of HIV/AIDS. The study concluded that sexual behaviour, knowledge, occupation, family history, and marital status have a significant relationship with the incidence of HIV/AIDS. This study suggests the need for early education and socialisation starting from the junior high school level, there needs to be peer support groups in collaboration with the government and the private sector related to HIV / AIDS sufferers, there needs to be free caten examination related to HIV / AIDS